Seoul Virus Infection and Spread in United States Home-Based Ratteries: Rat and Human Testing Results From a Multistate Outbreak Investigation. (2nd June 2020) - Knust, Barbara; Brown, Shelley; de St. Maurice, Annabelle; Whitmer, Shannon; Koske, Sarah E; Ervin, Elizabeth; Patel, Ketan; Graziano, James; Morales-Betoulle, Maria E; House, Jennifer; Cannon, Deborah; Kerins, Janna; et al.
Abstract: Background: During 2017, a multistate outbreak investigation occurred after the confirmation of Seoul virus (SEOV) infections in people and pet rats. A total of 147 humans and 897 rats were tested. Methods: In addition to immunoglobulin (Ig)G and IgM serology and traditional reverse-transcription polymerase chain reaction (RT-PCR), novel quantitative RT-PCR primers/probe were developed, and whole genome sequencing was performed. Results: Seventeen people had SEOV IgM, indicating recent infection; 7 reported symptoms and 3 were hospitalized. All patients recovered. Thirty-one facilities in 11 US states had SEOV infection, and among those with ≥10 rats tested, rat IgG prevalence ranged 2%–70% and SEOV RT-PCR positivity ranged 0%–70%. Human laboratory-confirmed cases were significantly associated with rat IgG positivity and RT-PCR positivity ( P = .03 and P = .006, respectively). Genomic sequencing identified >99.5% homology between SEOV sequences in this outbreak, and these were >99% identical to SEOV associated with previous pet rat infections in England, the Netherlands, and France. Frequent trade of rats between home-based ratteries contributed to transmission of SEOV between facilities. Conclusions: Pet rat owners, breeders, and the healthcare and public health community should be aware and take steps to prevent SEOV transmission in pet rats and to humans. Biosecurity measures and diagnostic testing can prevent further infections. Abstract : An investigation of Seoul virus infections in pet rats and people in the US found 31 infected facilities and 17 people with recent infections—all recovered with 3 hospitalized. Frequent trade of rats contributed to transmission of SEOV between facilities.